2021
DOI: 10.3390/ijerph18147621
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Susceptibility to and Seriousness of COVID-19: Associations of Risk Perceptions with Changes in Smoking Behavior

Abstract: During the COVID-19 pandemic, studies have documented increased and decreased cigarette smoking among adults. Individual differences in the perceived susceptibility and seriousness of the virus, for people who smoke in general and for oneself personally, may relate to changes in smoking. Using the Health Belief Model (HBM) as a theoretical framework, we examined associations with self-reported increasing and decreasing smoking a lot during the COVID-19 stay-at-home period. Adults in 30 large U.S. cities who sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
(60 reference statements)
2
16
0
Order By: Relevance
“…Prospective studies are warranted to confirm these findings. Second, as in other related studies [1][2][3][4][5]19,38,39], our data were self-reported, which might have made them subject to social desirability bias. Third, the participants only reported whether they had increased smoking, not changed their smoking behaviors or decreased smoking since the pandemic.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Prospective studies are warranted to confirm these findings. Second, as in other related studies [1][2][3][4][5]19,38,39], our data were self-reported, which might have made them subject to social desirability bias. Third, the participants only reported whether they had increased smoking, not changed their smoking behaviors or decreased smoking since the pandemic.…”
Section: Discussionmentioning
confidence: 87%
“…Third, the participants only reported whether they had increased smoking, not changed their smoking behaviors or decreased smoking since the pandemic. This may have led to measurement error, because it is possible that some smokers both increased and decreased their level of smoking during the pandemic [39]. Prospective studies with repeated measures of smoking consumptions are needed in order to understand the complex relations between COVID-19-related factors and smoking behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, it seems that beliefs about the COVID-19 pandemic and vaccines are evolving within populations. Previous work has recommended that communication campaigns and awareness activities be continuous and intense to maintain a perception of the severity of COVID-19, rather than the emerging popular belief that COVID-19 is no longer a threat [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…To fill this knowledge gap, we measured the effects of destination guidance on social distancing intentions of tourists and explored the intrinsic dynamics and cognition processes of the social distancing behaviors of tourists in China. Among a wide variety of models to investigate the health behavior of individuals (e.g., health belief model, social cognition theory, and the theory of planned behavior) [21,22], the protection motivation theory (PMT) is one of the most comprehensive models used empirically. It explains how people cognitively assess a particular threat and perform protective behaviors [23].…”
Section: Introductionmentioning
confidence: 99%